PENGALAMAN PROGRAM BANTUAN MAKANAN DI MALAYSIA: KAJIAN DI PERTUBUHAN BUKAN KERAJAAN (NGO) TERPILIH: The Experience of Food Aid Programmes in Malaysia: A Case Study of Selected Non-Governmental Organizations (NGOs) - Hasan, Norzuraida; Ab Rahman, Asmak (Jurnal Syariah, 2012)
Food aid programmes constitute one of the strategies to address the problem of hunger and food insecurity among the poor and the needy. In Malaysia, the provision of food aid involves various parties, whether channelled through formal or informal institutions. Other than government bodies, it also involves non-governmental organizations (NGOs), corporate bodies, mosques and by individuals. However, the food aid programmes like soup kitchens are mostly undertaken by the NGOs. This paper examines the implementation of food aid programmes conducted by the NGOs in Malaysia, by focusing on PERTIWI Soup Kitchen and Free Food Centre, BELAMISKIN. In this article, the authors used field studies by observation and interview. The observation method was used while conducting research at the Free Food Centre BELAMISKIN. The interviews were conducted with the implementers of the food aid programmes in Malaysia. Data were analysed using content analysis based on themes using inductive, deductive and comparative methods. The findings indicate that food aid programmes are very helpful for the poor and needy, and, indirectly, could increase the level of food security.